A Stakeholder Approach to Corporate Social Responsibility: A Fresh Perspective into Theory and Practice - Jamali, Dima (Journal of business ethics, 2008)
Stakeholder theory has gained currency in the business and society literature in recent years in light of its practicality from the perspective of managers and scholars. In accounting for the recent ascendancy of stakeholder theory, this article presents an overview of two traditional conceptualizations of corporate social responsibility (CSR) (Carroll: 1979, ‘A Three-Dimensional Conceptual Model of Corporate Performance’, The Academy of Management Review 4(4), 497–505 and Wood: 1991, ‘Corporate Social Performance Revisited’, The Academy of Management Review 16(4), 691–717), highlighting their predominant inclination toward providing static taxonomic CSR descriptions. The article then makes the case for a stakeholder approach to CSR, reviewing its rationale and outlining how it has been integrated into recent empirical studies. In light of this review, the article adopts a stakeholder framework – the Ethical Performance Scorecard (EPS) proposed by Spiller (2000, ‘Ethical Business and Investment: A Model For Business and Society’, Journal of Business Ethics 27, 149–160) – to examine the CSR approach of a sample of Lebanese and Syrian firms with an interest in CSR and test relevant hypotheses derived from the CSR/stakeholder literature. The findings are analyzed and implications drawn regarding the usefulness of a stakeholder approach to CSR.